Demonstration of a coupled computational fluid dynamics approach for modelling non-water cooled small modular reactors. (1st September 2021) - Podila, K.; Colton, A.; Trottier, A.; Pfeiffer, P.; Chen, Q.; Rao, Y.; Sun, L.; Huang, X.; Waddington, G.
Highlights: Application of high-fidelity multi-physics coupled tool set showcased for modelling SMRs. Technology agnostic approach adopted within the analyses. Molten salt and gas cooled reactor configurations tested. Reactivity insertion and pump trip scenarios modelled for MSRs. FOAK analyses expected to address some of the existing modelling gaps. Abstract: This paper provides an overview of the capabilities of a new toolset that is being developed at Canadian Nuclear Laboratories for modelling advanced non-water cooled small modular reactor concepts. Throughout the study, a technology agnostic approach was adopted. The integrated toolset includes computational fluid dynamics, neutronics and system thermalhydraulics codes to handle a range of multi-physics capabilities. The toolset has been applied to two different non-water cooled SMR concepts: molten salt and prismatic gas-cooled reactors. A step-wise approach was used in which the models were first tested using standalone codes, followed by execution of coupled-code simulations. This paper demonstrates the application of the toolset to gas-cooled and molten-salt reactor concepts, including transient simulations using the CFD code STAR-CCM+ coupled with the Monte Carlo neutronics code Serpent 2 and with the system thermalhydraulics code RELAP5-3D. The scenarios considered include a step reactivity insertion and a pump trip for the molten salt reactors. Overall, the results obtained so far demonstrates the potential of the developed methodology at CNL in simulating the non-water cooled concepts.